Chilancho of Kirtipur: A Unique Secret Site - Sigdel, Gopal Prasad (International Research Journal of MMC, 2025)
This study aims to elucidate the importance of Jagatpal Mahavihar and Chilancho Caitya picturizing their historical and socio-religious dimensions. Then the paper explores ritual, cultural, artistic and archeological features and endeavoring to introduce the secrete sites among the local, national and global communities. The study employs qualitative approach, sequentially analyzing historical artifacts and religious practices to construct its holistic profile. The research grasps the secondary resources such as historical text, archeological reports, journal articles, Newar Buddhist heritages and local religious rites along with regular and traditional practices of Buddhist devotees in the shrines. Three key informants and interviews were conducted and analyzed correlating its attributes, historical developments, spiritual functions and assessing its uniqueness within local and global contents. This paper presents the strength of Chilancho living heritage and sacred sites but lesser known introducing its key uniqueness tantalizing subaltern perspective for further research.